Poesia é isso e aquilo: um estudo das reflexões metapoéticas na poesia de Sebastião Uchoa Leite - Silveira, Juliana Fabrícia da [UNESP] (2015)
This work has as main objective to study of metalanguage present in the poetry of Sebastião Uchoa with focus in their first four books, namely: Dez sonetos sem matéria (1958-1959), Exercícios numa mesa sobre o tempo e o espaço (1958 -1962 ), Signos/Gnosis e outros ( 1963-1970 ) and Antilogia ( 1972-1979 ) . The metalanguage has a unique way to manifest in each of these works and reveals a complex process of poetic developed. The thesis is divided in four chapters in which each is dedicated to a poet's book. The creative reason can be considered one of the problematic cores for the study of metalanguage in sebastiana poetry as it questions the whole time the results of the literary work, often with suspicion and frustration. Beside the reason emerge archetypes and figures that should act as facilitators for the creative work of self - lyrical, however, seem more difficult their work than actually encourage it